Studies on Viroid Shed Light on the Role of RNA Three-Dimensional Structural Motifs in RNA Trafficking in Plants - Ma, Junfei; Wang, Ying (Frontiers in Plant Science, 2022)
RNAs play essential roles in various biological processes. Mounting evidence has demonstrated that RNA subcellular localization and intercellular/systemic trafficking govern their functions in coordinating plant growth at the organismal level. While numerous types of RNAs (i.e., mRNAs, small RNAs, rRNAs, tRNAs, and long noncoding RNAs) have been found to traffic in a non-cell-autonomous fashion within plants, the underlying regulatory mechanism remains unclear. Viroids are single-stranded circular noncoding RNAs, which entirely rely on their RNA motifs to exploit cellular machinery for organelle entry and exit, cell-to-cell movement through plasmodesmata, and systemic trafficking. Viroids represent an excellent model to dissect the role of RNA three-dimensional (3D) structural motifs in regulating RNA movement. Nearly two decades of studies have found multiple RNA 3D motifs responsible for viroid nuclear import as well as trafficking across diverse cellular boundaries in plants. These RNA 3D motifs function as “keys” to unlock cellular and subcellular barriers and guide RNA movement within a cell or between cells. Here, we summarize the key findings along this line of research with implications for future studies on RNA trafficking in plants.